Analisis Kesuksesan Aplikasi Mobile CRM Menggunakan Metode DeLone and McLean: Studi Kasus - Rakhman, Shinta Oktaviana (MULTINETICS, 2023)
The CRM mobile application at PT XYZ is designed as an application that can make it easier for users to monitor their heavy equipment in order to obtain information and assist customer business operations. The purpose of this study is to determine the success rate of mobile applications and which variables most influence user satisfaction. This study empirically examines the success of mobile applications using the DeLone and McLean information system success model by analyzing information system success consisting of elements of information quality, system quality, service quality, usage, user satisfaction, and net benefits. Data collection is carried out by providing questionnaires via Google Form to customers who use mobile applications. This research method uses Structural Equation Modeling (SEM) with the Partial Least squares (PLS) approach and SmartPLS 4.0 software to analyze the data. Based on the results of the analysis, it can be concluded that of the 8 hypotheses, there are 4 proven acceptable, namely the variable information quality on user satisfaction, system quality on usage, service quality on user satisfaction, and user satisfaction on net benefits.